A Systematic Review of Interventions to Promote Self-Determination for Students With Extensive Support Needs. (March 2023) - Alsaeed, Abdulaziz; Mansouri, Mary Curran; Shogren, Karrie A.; Raley, Sheida K.; Kurth, Jennifer A.; Leatherman, Elizabeth M.; Lockman Turner, Elissa
Intervening to enhance self-determination has been linked to enhanced in-school outcomes (e.g., academic and transition goal attainment and access to general education) and post-school outcomes (e.g., competitive employment, community participation) for students with and without disabilities in inclusive schools. However, research is needed to examine the extent to which students with extensive support needs (ESN) are included in this body of research. This systematic review aims to identify empirical research articles that examined the outcomes of interventions designed to promote abilities and skills associated with self-determination for students with ESN. Results suggest that research on self-determination for students with ESN in school contexts is limited across grade levels, particularly in inclusive settings. Consequently, there is a need for ongoing research to consider effective self-determination assessments to inform the design and implementation of interventions that promote self-determination for students with ESN in inclusive settings. Implications for research and practice are discussed.